Collaboration of Non-formal Higher Education Management in Five Provinces of Southern Thailand - Hanghon, Pornpichet; Dhammasaccakarn, Wanchai (WMS Journal of Management, 2018)
This research aims to study indicators and collaboration components between local administrative organizations (LAOs) and community learning centers (CLCs) in non-formal higher education management in southern Thailand, synthesize and propose policy to encourage the collaboration between both organizations. The research methodology is a combination of three phases of mixed methods: firstly, qualitative research by group interviews, secondly, quantitative research employed 500 questionnaires, analyzed the basic statistics and factor analysis (exploratory and confirmatory), and thirdly, qualitative research, conducting group discussions. The study was conducted from 4 groups: LAO chiefs, teachers, CLC committees, and students, from 18 CLCs of 5 provinces: Chumphon, Suratthani, Krabi, Nakhonsithammarat, and Songkhla. The study found that there are 60 indicators of 8 each sub-factor in 4 each main-factors (standardization, formalization, reciprocity, and intensity), the linear structural model was in statistically significant congruence with empirical data, and the propose policy to encourage the collaboration that The Department of Local Administration directed to encourage local administrative organizations to intend the importance of education for local people, and apply the confirmatory factor analysis results to adjust 3 stages: adjusting the synchronization concept, the mutual collaboration, and a partnership, to be flexible and have sufficient budget.